Tinjauan Kenyamanan Termal pada Rumah Tradisional Aceh - Raudhatul Jannah; Marlisa Rahmi; Riza Aulia Putra (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
This research reviews thermal comfort in the aspects of ventilation and lighting in Aceh Houses in Pidie Regency, based on residents' perceptions. Acehnese houses, as traditional architecture, have natural and artificial ventilation and lighting systems that are considered adequate. This research uses a qualitative approach with a case study method, involving field observations, interviews, and documentation in five sub-districts: Mutiara, Mutiara Timur, Glumpang Tiga, Peukan Baro, and Delima. Next, the data col-lected will be analyzed descriptively using coding.